2022
DOI: 10.32677/ijch.2017.v04.i02.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in early prediction of severity of dengue infection

Abstract: Background: Dengue has become a major international health problem in recent years. As per the World Health Organization, dengue has shown a 30-fold increase globally over the past five decades, and approximately, 50-100 million new infections are estimated to occur annually in more than 100 endemic countries. Objective: To evaluate the sonographic findings in children with dengue fever (DF) and to determine its role in predicting the severity of the disease. Methods: One hundred and twenty dengue serology-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…There was a similar finding in the study by Pothepragada S, et al 25 on univariate analysis. Unlike the present study, a study by Malleshappa K, et al 20 suggested ascites and pleural effusion were not significantly associated with SD. They found perinephric oedema was significantly associated with dengue severity.…”
Section: Discussioncontrasting
confidence: 99%
“…There was a similar finding in the study by Pothepragada S, et al 25 on univariate analysis. Unlike the present study, a study by Malleshappa K, et al 20 suggested ascites and pleural effusion were not significantly associated with SD. They found perinephric oedema was significantly associated with dengue severity.…”
Section: Discussioncontrasting
confidence: 99%